The primary goal of monetary policy: Reflections on the nature of the problem - Adam Hetmańczuk (The Central European Review of Economics and Management (CEREM), 2021)
Aim: In this article, the state of the discourse concerning the final goal of the modern central bank is presented, in particular the aim of price stability, understood as low and stable inflation. Design/Research methods: The article was prepared on the basis of scientific publications in the field of monetary policy as well as materials and documents from different central banks, including the US Federal Reserve System and the European Central Bank. Conclusions/findings: Low and stable inflation reduces uncertainty about future price developments. This facilitates decision-making for companies concerning production and investment, and for households concerning consumption and saving. From a macroeconomic point of view, price stability is a prerequisite for the efficient functioning of the economy and for achieving high growth rates. In practice, the need for a quantifiable definition has been disregarded, while only a descriptive and qualitative definition of price stability is insufficient for an effective monetary policy and the implementation of the anti-inflationary mission by the central bank.
Keywords: E31; E51; E52; E58; 330; central bank; monetary policy; price stability; inflation